Unravelling Memories of Family Separation Among Sri Lankan Tamils Resettled in Australia, 1983–2000. Issue 2 (4th May 2018) - Kandasamy, Niro
Abstract: Using life story interviews with 10 Sri Lankan Tamil refugees resettled in Australia, this article shows how family separation in experiences of civil war and resettlement produce long-lasting and emotional memories of fear and determination. The findings explore how young Tamil people gave meaning to family when they interacted with key individuals and negotiated cultural practices in different spaces. Moreover, intergenerational family narratives emerged as a key practice through which Tamils preserved the family identity. The analysis demonstrates how and when family separation can manifest in personal memories to reveal stories of agency and resilience. A critical engagement of the past can help to better understand concepts of childhood in relation to family and family separation in war affected diaspora communities.